Theoretical and experimental investigation of low-volgage and low-loss 25-Gbps Si photonic crystal slow light Mach–Zehnder modulators with interleaved p/n junction - Terada, Yosuke; Ito, Hiroyuki; Nguyen, Hong C.; Baba, Toshihiko (Frontiers in Physics, 2014)
In this study, we investigated the performance of Si lattice-shifted photonic crystal waveguide (LSPCW) Mach-Zehnder modulators theoretically and experimentally. The LSPCW increases the phase shift in modulator to 2.3 - 2.5 times higher, which allows for size reduction and high performance. On-chip passive loss was reduced to less than 5 dB by optimizing each component. We obtained 25 Gbps clear open eye and 3 dB extinction ratio at a drive voltage of 1.5 – 1.75 V for 200 μm phase shifter with linear p/n junction when we added a modulation loss of 7 dB. This modulation loss was reduced to 0.8 dB, maintaining other performance, by employing interleaved p/n junction and optimizing doping concentrations.